2009
DOI: 10.1530/rep-08-0237
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic characteristics and fertility of murine spermatozoa collected in different solutions

Abstract: Osmotic stress is an important factor that can result in cell damage during cryopreservation. Before ejaculation or collection for cryopreservation, murine spermatozoa are stored in epididymal fluid, a physiologically hyperosmotic environment (w415 mmol/kg). The objectives of this study were to determine the osmotic tolerance limits of sperm motion parameters of ICR and C57BL/6 mouse spermatozoa collected in isosmotic (290 mmol/kg) and hyperosmotic (415 mmol/kg) media, and the effect of the osmolality of sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Experiments in our laboratory (Garcia et al 2012) and others (Pommer et al 2002) have demonstrated that this osmotic roller coaster is more detrimental for stallion spermatozoa than continuous exposure to a given hyperosmolar solution. Similar results were found in other species such as rhesus monkey (Rutllant et al 2003), mouse (Si et al 2009) and bull sperm (Guthrie et al 2002), among others. Furthermore, the addition of permeating cryopretectans also creates an anisosmolar environment for the spermatozoa, causing the cells to shrink or swell.…”
Section: Factors Affecting the Integrity Of The Sperm Membranesupporting
confidence: 90%
See 1 more Smart Citation
“…Experiments in our laboratory (Garcia et al 2012) and others (Pommer et al 2002) have demonstrated that this osmotic roller coaster is more detrimental for stallion spermatozoa than continuous exposure to a given hyperosmolar solution. Similar results were found in other species such as rhesus monkey (Rutllant et al 2003), mouse (Si et al 2009) and bull sperm (Guthrie et al 2002), among others. Furthermore, the addition of permeating cryopretectans also creates an anisosmolar environment for the spermatozoa, causing the cells to shrink or swell.…”
Section: Factors Affecting the Integrity Of The Sperm Membranesupporting
confidence: 90%
“…Similar results were found in other species such as rhesus monkey (Rutllant et al. 2003), mouse (Si et al. 2009) and bull sperm (Guthrie et al.…”
Section: Factors Affecting the Integrity Of The Sperm Membranesupporting
confidence: 88%
“…Please cite this article in press as: Tamayo instance, Si et al (2009) obtained higher fertility when caused by hypo-osmotic stress when epididymal sperma-382 tozoa endure the freezing process.…”
Section: Discussionmentioning
confidence: 99%
“…Less attention has been focused on the environmental sensitivity of spermatogenesis, however, several studies have shown adverse effects of in vitro and in vivo environments on sperm motility, 51 , 52 DNA breakage 53 and apoptosis 54 . These changes have been further associated with alterations in DNA methyltransferase expression and transgenerational inheritance of altered phenotype 54 , 55 .…”
Section: Gametogenesismentioning
confidence: 99%